2001
DOI: 10.1037/0021-9010.86.6.1294
|View full text |Cite
|
Sign up to set email alerts
|

Turnover and organizational performance: A comparative analysis of the effects of voluntary, involuntary, and reduction-in-force turnover.

Abstract: Data were collected from 31 regional subunits of a national financial services company to examine differential effects of 3 types of turnover (voluntary, involuntary, and reduction-in-force) on measures of organizational subunit performance. Although each form of turnover exhibited adverse effects on subunit performance when examined separately, partial correlation results revealed greater and more pervasive adverse effects for reduction-in-force turnover (i.e., downsizing) in comparison with the effects of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(188 citation statements)
references
References 29 publications
3
177
0
8
Order By: Relevance
“…These turnover-profit effects were conditional on a process conformance moderator, were curvilinear, and were sensitive to the turnover aggregation window. McElroy et al (2001) found negative correlations between three turnover measures (voluntary, involuntary, and reduction in force) and same-year profitability, yet only involuntary turnover remained statistically significant when controlling for size, location, and service mix. Time-lagged relationships were somewhat weaker, as only reduction in force turnover remained negative and statistically significant in both the zero-order and partial correlation analyses.…”
Section: Firm Performancementioning
confidence: 96%
“…These turnover-profit effects were conditional on a process conformance moderator, were curvilinear, and were sensitive to the turnover aggregation window. McElroy et al (2001) found negative correlations between three turnover measures (voluntary, involuntary, and reduction in force) and same-year profitability, yet only involuntary turnover remained statistically significant when controlling for size, location, and service mix. Time-lagged relationships were somewhat weaker, as only reduction in force turnover remained negative and statistically significant in both the zero-order and partial correlation analyses.…”
Section: Firm Performancementioning
confidence: 96%
“…Turnover in itself is not necessarily detrimental to an organization as the exit of underperforming employees can be beneficial (Abelson & Baysinger, 1984;McElroy, Morrow, & Rude, 2001). In general, however, turnover has been shown to have a negative effect on organizational performance (Hancock, Allen, Bosco, McDaniel, & Pierce, 2013;Park & Shaw, 2013).…”
Section: Voluntary Turnovermentioning
confidence: 99%
“…Firms typically respond to adverse business conditions by downsizing, thereby losing valuable human capital with potentially adverse effects on firm performance (Cascio, 2002;McElroy et al, 2001). Real options theory recommends that firms should develop capabilities, i.e.…”
Section: Options and Human Resource Managementmentioning
confidence: 99%